Application of innovative technologies in teachingкazakh language (Eurasian Journal of Philology Science and Education, 2016)
This article discusses the importance of using innovative technologies in teaching Kazakh language in classrooms with non-Kazakh language learning. One of the main tasks set before the Kazakhstani system of higher education in fulfilling the state order for training specialists, the application and implementation of innovative technologies in the educational process. The article describes the characteristics and types of universities that work in innovative directions. The article talks about two aspects of Internet use in the classroom. Recommendations are given about the uses of the computer and telecommunicational technology in the classroom on the Kazakh language. The efficiency of online lessons is considered on the example of practical training. The possibilities, effective methods, current status and the problems of using distance learning systems. Examines the characteristics of effective distance learning. Along with this, the article considers the place of educational television in teaching Kazakh language.
Keywords: innovative technology; internet; website; online lessons; virtual training; educational television.